COLLABORATIVE WRITING IN EFL CONTEXT: A LITERATURE REVIEW OF RESEARCH REPORTS IN THE LAST DECADE* - Susanti, Ani (Institut Hindu Dharma Negeri Denpasar, 2018)
The 4 Cs 21st century skills framework has included collaboration as one of the critical skills for now and future generation living. In EFL context, studies about collaboration are often connected with collaborative writing (CW). This strategy has been more popular especially in higher education as academic writing and collaboration skills development strategy. Numbers of studies reported not only the outcome but also the process of collaborative writing. This paper synthesizes research reports in the last decade collected from online publication including unpublished thesis and dissertation as well as articles in journals related to language education. Inspired by Dillenbourg (1996), this synthesis report is organized into four dimensions; focus on effect, condition, interaction, and technology use. Finally, some possible future research questions are pointed out. Keywords: collaboration, academic writing, Collaborative Writing, EFL, higher education